2008
DOI: 10.1002/sca.20085
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Latex Particle Size Control for Improved Water Blush Resistance

Abstract: Latex films have a tendency to "blush" when exposed to water. The swelling of trapped hydrophilic material, which results in pockets with different refractive indices, is proposed as a possible model for blushing. A pressure-sensitive latex was developed on the basis of this model. The blush was improved by the choice of the surfactant and control of the particle diameter. The resulting latex has an unusual particle growth behavior during polymerization. The particle size distribution (PSD) was characterized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…This is the origin of water whitening of latex film. Naturally, this phenomenon is not expected to occur in markets and applications such as film labels, including bottle labels, shampoo labels, food labels, and so forth …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the origin of water whitening of latex film. Naturally, this phenomenon is not expected to occur in markets and applications such as film labels, including bottle labels, shampoo labels, food labels, and so forth …”
Section: Introductionmentioning
confidence: 99%
“…Naturally, this phenomenon is not expected to occur in markets and applications such as film labels, including bottle labels, shampoo labels, food labels, and so forth. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] To this end, different approaches have been developed to improve the water whitening resistance of latex films, such as using polymerizable or reactive surfactants, [17][18][19] macromolecular surfactant, 20 no surfactant, 21 increasing the density of the polymer network by using crosslinking agents, 22,23 removing watersoluble species by centrifugation, dialysis, precipitation, using ion exchange resins, and so forth, 24,25 adjusting the pH of the emulsion, copolymerizing fluoride monomers 26,27 preparation of polymer latex with multiple layer core-shell structure, and so forth. 28 The main components of a polyacrylate emulsion include soft and hard monomers, as well as small amount of functional monomers.…”
Section: Introductionmentioning
confidence: 99%
“…Surfactants that are strongly adsorbed during the film formation process can also be trapped at particle/particle boundaries creating hydrophilic pathways in the film, and in some cases, the surfactant is pushed away from the particle/particle boundaries creating small pockets or aggregates throughout the film . As water is drawn into the film by osmotic forces, the existence of hydrophilic pockets can result in localized defects such as discoloration and blistering because the hydrophilic pockets will swell when exposed to water . The swollen pockets usually have a refractive index different from that of the polymer, and hence they scatter light and the film becomes cloudy or white …”
Section: Introductionmentioning
confidence: 99%
“…As water is drawn into the film by osmotic forces, the existence of hydrophilic pockets can result in localized defects such as discoloration and blistering because the hydrophilic pockets will swell when exposed to water . The swollen pockets usually have a refractive index different from that of the polymer, and hence they scatter light and the film becomes cloudy or white …”
Section: Introductionmentioning
confidence: 99%
“…In this respect, we selected NPPHEO10 (polyoxyethylene 4-nonyl-2-propylene-phenol) as a nonionic reactive surfactant to modify its chemical structure with MA to produce maleate ester and adduct, which were designated as NME and NMA, respectively. It has been reported that an anionic reactive surfactant polyoxyethylene 4-nonyl-2prpylene-phenyl ether ammonium sulfate and their derivatives are widely used as anionic polymerizable surfactants in emulsion polymerization reactions [29][30][31][32], while nonionic NPPhEO10 has not been used as a polymerizable surfactant. The present work aims to modify the chemical structure of NPPhEO10 to be used as a stabilizer for emulsion polymerization systems.…”
Section: Resultsmentioning
confidence: 99%